The Contribution of Gambier (Uncaria gambir Roxb.) Income to Farmers’ Households Income in Pesisir Selatan District: Kontribusi Gambier (Uncaria gambir Roxb.) Pendapatan terhadap Pendapatan Rumah Tangga Pesisir Kabupaten Pesisir Selatan - Azriani, Zednita; Melinda Noer; Yuerlita; Yusmarni (Jurnal Riset Perkebunan, 2024)
Gambier productivity in Pesisir Selatan District is low, affecting gambier farmers' household income. Furthermore, the price of gambier fluctuates, especially between 2019 and 2022. This study aims to describe gambier cultivation carried out by farmers in Pesisir Selatan and analyze the contribution of gambier income to farmers' household income in Pesisir Selatan. This descriptive study used the survey approach on two districts of gambier-producing centers in Pesisir Selatan, namely Koto XI Tarusan and Sutera Sub-district. The sample size is sixty farmers, who were chosen using a purposive sampling strategy based on the criteria of farmers who have harvested their gambier. The data gathered include gambier farming activities, markets, production, revenue, costs, gambier income, and household income. The findings revealed that weeding and pest spraying were done three times each year on average. Farmers fertilize their crops between two and four times every year. Harvesting was also done 2-4 times a year. Gambier production averaged 899.83 kg each period, or 2,384.56 kg per year. The gambler's average selling price was Rp. 41,250, -/kg. The average gambier revenue each year was Rp 98,363,031.25, -. The annual income from the gambier business was Rp. 21,656,558.34, - or Rp. 1,804,713.19, - per month. Farmers' total annual revenue was Rp. 59,911,051.33, - or Rp. 4,992,587.61, - per month. Gambier contributed 36% of the total household income in Pesisir Selatan. Gambier farmers in Pesisir Selatan do not just grow gambier for a living. Rice farming and oil palm plantations provide additional household income.